Sperm DNA fragmentation in Chinese couples with unexplained recurrent pregnancy loss - Zhu, Xiao-Bin (Asian J Androl, 2019)
We aimed to study the association between sperm DNA fragmentation and recurrent pregnancy loss (RPL) in the Chinese population via a retrospective observational study of Chinese couples who had experienced RPL between May 2013 and August 2018. The study population included 461 men from couples with RPL and 411 men from a control group (couples with clinical pregnancy via in vitro fertilization owing to female causes). Routine semen analysis, sperm chromatin analysis, and microscopic (high-power) morphological analysis were performed using semen samples. Semen samples were assessed for volume, sperm count, and motility. The sperm DNA fragmentation index (DFI) was calculated, and the median DFI was obtained. Men were categorized as having normal (37.8%; DFI ≤ 15.0%), moderate (33.6%; 15.0% < DFI < 30.0%), or severe (28.6%; DFI ≥ 30.0%) DNA fragmentation levels. The percentage of men with severe DNA fragmentation was significantly higher in the RPL (42.3%) group than that in the control group (13.1%), whereas the percentage of men with normal levels of DNA fragmentation was significantly lower in the RPL group (22.8%) than that in the control group (54.7%). Subsequent analysis also demonstrated that the sperm DNA fragmentation rate had a moderate reverse correlation with the sperm progressive motility rate (r = −0.47, P < 0.001) and the total motile sperm count (r = −0.31, P < 0.001). We found a positive correlation between RPL and sperm DNA fragmentation. The results suggest that increased sperm DNA damage is associated with RPL.